May the best duke win - Belgado, Paulia (Harlequin historicals., 2022)
She must marry a duke But which one? American heiress Kate Mason loves being a rail engineer-yet her father is demanding she marry an English aristocrat! Her plan is to accept any noble who'll allow her to pursue her railway ambitions-until she kisses Sebastian, Duke of Mabury. He is a duke, but the wrong one. He's shunned society since a family scandal and vowed never to wed at all. So why does being with him feel so right?